Effects of Yoga Practice on Stress Levels: A Comprehensive Analysis - Apta Mylsidayu; B Bujang; Elly Diana Mamesah (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Individuals typically have dual effects when experiencing stress, namely a physical manifestation influencing their well-being during stressful episodes and a psychological impact characterized by cognitive, emotional, and behavioural symptoms. The objective of this investigation was to scrutinize the variables exerting influences on stress. Employing a cross-sectional analytical design, this study considered age, gender, employment position, and the duration of yoga practice as independent variables, while stress levels served as the dependent variable. The research involved 20 individuals who participated in a questionnaire test, supplemented by an additional 30 individuals serving as research subjects. The study population were 50 members drawn from fitness centres located in West Jakarta. The data collection relied on the Kessler Psychological Distress Scale questionnaire, probing into facets, such as age, gender, employment situations, and the frequency of yoga practice. The distribution of questionnaires used the Google Forms platform, administered by researchers presented at the research site. Employing a multiple linear regression as the method of data analysis, computations were executed through the JAMOVI statistical program. The findings of this study revealed a negative correlation between age, gender, employment situations, and the duration of yoga practice with stress levels. It suggests that these factors collectively contribute to the reduction in stress levels. However, despite a discernible 23.5 percent difference in stress levels, the impact remains inconspicuous.